2018
DOI: 10.26434/chemrxiv.7323995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CuH-Catalyzed Enantioselective Alkylation of Indole Derivatives with Ligand-Controlled Regiodivergence

Abstract: <b>Enantioenriched molecules bearing indole-substituted stereocenters form a class of privileged compounds in biological, medicinal, and organic chemistry. Thus, the development of methods for asymmetric indole alkylation is highly valuable in organic synthesis. Traditionally, achieving N-selectivity in indole alkylation reactions is a significant challenge, since there is an intrinsic preference for alkylation at C3, the most nucleophilic position. Furthermore, selective and predictable access to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…These results are consistent with the previously studied ligand effects, where Ph-BPE ligand promoted the formation of C3-alkylated product. 7 In the reaction with the indazole electrophile (1a), we found that the SN2′ oxidative addition (TS3) requires a higher activation barrier of 28.0 kcal/mol with respect to 10, when compared to the reaction with indole (TS3′), and the product is thermodynamically destabilized by 3.6 kcal/mol (12 versus 12′). Since the C3 oxidative additions are endergonic, the transition states are more product-like and exhibit significant N−O bond elongations (Figure 3B).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These results are consistent with the previously studied ligand effects, where Ph-BPE ligand promoted the formation of C3-alkylated product. 7 In the reaction with the indazole electrophile (1a), we found that the SN2′ oxidative addition (TS3) requires a higher activation barrier of 28.0 kcal/mol with respect to 10, when compared to the reaction with indole (TS3′), and the product is thermodynamically destabilized by 3.6 kcal/mol (12 versus 12′). Since the C3 oxidative additions are endergonic, the transition states are more product-like and exhibit significant N−O bond elongations (Figure 3B).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Initially, we attempted the coupling of a variety of readily accessible alkenes with indazole 1a under the conditions previously developed for indole alkylation. 7 Less than 5% yield of the alkylated indazole products were formed in the cases of styrene (Figure 2a). However, when cyclohexylallene was employed, 11 it reacted efficiently with the indazole electrophile 1a, providing the corresponding allyl indazole product (3s) in good yield with a high level of enantioselectivity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unfavorable interactions lead to elongation of the forming C-C bond, which results in a later transition state, when compared to the reactions with the intermediate 7 as it can be observed both from the forming C-C bond, as well as the breaking C-Cu bonds. As oxidative addition mechanisms have been proposed to be operative in the indole alkylation reaction reported earlier, 22 we investigated this pathway from the most stable intermediate 7, leading to the cationic Cu III complex with copper bound to the either C (9) or N (10) of the indazole. Both oxidative addition transition states TS3, TS4 were found to be disfavored relative to TS2c (ΔΔG ‡ = 7.0, 12.9 kcal/mol respectively).…”
Section: Additional Computational Resultsmentioning
confidence: 99%
“…In particular, Buchwald and coworkers have recently documented on the copper catalyzed activation of N‐ benzoyloxy‐ indoles 63 and subsequent trapping with in‐situ generated chiral alkyl‐copper reagents (L‐Cu(OAc) 2 /Silane/alkene) . Regiodivergence towards N(1)‐ or C(3)‐functionalization was effectively recorded via selection of chiral organo ligands.…”
Section: N‐leaving Group Indolesmentioning
confidence: 99%